The Experimental MJO Prediction Project - Waliser, Duane; Weickmann, Klaus; Dole, Randall; Schubert, Siegfried; Alves, Oscar; Jones, Charles; Newman, Matthew; Pan, Hua-Lu; Roubicek, Andres; Saha, Suranjana; Smith, Cathy; Van Den Dool, Huug; et al. (Bulletin of the American Meteorological Society, 2008)
Weather prediction is typically concerned with lead times of hours to days, while seasonal-to-interannual climate prediction is concerned with lead times of months to seasons. Recently, there has been growing interest in “subseasonal” forecasts—-those that have lead times on the order of weeks (e.g., Schubert et al. 2002; Waliser et al. 2003; Waliser et al. 2005). The basis for developing and exploiting subseasonal predictions largely resides with phenomena such as the Pacific North American (PNA) pattern, the North Atlantic oscillation (NAO), the Madden–Julian Oscillation (MJO), mid-latitude blocking, and the memory associated with soil moisture, as well as modeling techniques that rely on both initial conditions and slowly varying boundary conditions (e.g., tropical Pacific SST). An outgrowth of this interest has been the development of an Experimental MJO Prediction Project (EMPP). Th project provides real-time weather and climate information and predictions for a variety of applications, broadly encompassing the subseasonal weather–climate connection. Th focus is on the MJO because it represents a repeatable, low-frequency phenomenon. MJO’s importance among the subseasonal phenomena is very similar to that of El Niño–Southern Oscillation(ENSO) among the interannual phenomena. This note describes the history and objectives of EMPP, its status, capabilities, and plans. NASA/JPL